Carbon derived from treated rice husk as fuel for direct carbon fuel cells. (15th March 2022) - Yue, Shuai; Cui, Can; Wei, Keyan; Jiang, Yao; Bai, Zhichuan; Ma, Jianjun; Patabendige, Chami N.K.; Jiang, Cairong
Summary: Direct carbon fuel cell (DCFC), as an environmentally friendly technology, strives to reduce polluting gas emissions, in the meanwhile, which can raise the value of preferably sustainable resources. In this work, an abundant and cheap resource‐rice husk is selected as fuel and treated with HCl, citric acid, and NaOH to evaluate the application in Solid Oxide (SO)‐DCFC. Co‐treatment of acid and alkali removes the ash and increases the carbon content of rice husk, and also introduces the oxygen‐containing functional groups on the surface, thus cell performance is enhanced. In particular, the cell using acid and alkali co‐treated husk carbon is capable of operating up to 100 hours under 0.7 V at 750°C. Abstract : The electrochemical performance of rice husks with different pretreatment methods performed in SO‐DCFC is compared in this paper. Co‐treatment of rice husk with acid and alkali effectively removes the ash and increases the content of carbon and oxygen, leading to an improvement of the output power and a good durability of up to 100 hours under 0.7 V at 750°C.